Female blind baseball players against gender discrimination: the “red diamonds” experience - Carretti, Giuditta; Russo, Pippo; Manetti, Mirko; Marini, Mirca (Frontiers in Sports and Active Living, 2024)
Sport has the well-known power of improving body awareness, self-esteem and social interaction thus promoting quality of life and psychophysical well-being. Specifically referring to adapted disciplines, habitual practice often becomes an effective integration and self-efficacy booster. Among disabilities, visual impairment deeply alters body image perception, autonomy, and environmental/social interaction heavily reducing sport or leisure involvement opportunities. In particular, visually impaired women represent one of the most vulnerable categories to gender and disability discrimination. Moreover, even when congenitally sightless, they perceive social pressure of mainstream beauty ideals, mostly spread by media, comparable to their sighted peers. On these premises and the previously demonstrated psychophysical benefits of Italian blind baseball practice on this target population, the present study aimed to deepen the social and educative potentialities of such adapted sport applying a more sociological research approach. The "red diamonds" event, namely the first-ever female blind baseball match, was the setting for the administration of our structured online survey. In detail, our survey comprised different evaluation tools such as the 18-item Psychological Well-Being Scale, the 12-item Short Form questionnaire, the Dresden Body Image questionnaire, the Rosenberg Self-Esteem Scale, and sociological model designed questions. Quality of life, psychological well-being, selfesteem, body image, and perceived female sport psychological violence were investigated in the whole women sample voluntarily adhering to the game. Survey results revealed no statistically significant differences between visually impaired players and sighted on-field subjects (i.e., coaches, assistants, and referees) in almost all the inquired variables, thus remarking the social and functional benefits of adapted sport through the "dual embodiment" and empowerment phenomenon. Given that the event was inspired by and performed on the World Day against women violence, our study deepened not only the topic of disability discrimination but also the currently alarming gender-related one. In such a context, the present research might provide interesting cues for further investigations on disability and gender disparities in sport, hence spreading interest in this under-investigated field. In perspective, the "red diamonds" experience could also contribute inspiring and progressively developing educative tools against any kind of discrimination by promoting integration and social growth through regular sport practice.